Meningkatkan Hasil Belajar Kosakata Bahasa Arab: Pengaruh Metode Problem Based Learning Abad 21 - Al-Rafi'i, Mushthafa Shadiq; Nursyamsyiah, Nunung; Supriadi, Rinaldi (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – In recent years, challenges have persisted in the acquisition of Arabic vocabulary among students, and one contributing factor to this issue is the perceived monotony of the existing learning methods. Consequently, the objective of this study is to investigate the impact and efficacy of implementing the PBL method in the process of learning Arabic vocabulary.Method – The research employed an experimental approach with a quasi-experimental design utilizing a Non-Equivalent Control Group Design scheme. The selection of the experimental and control groups did not involve a random process. Data collection encompassed both testing and non-testing methods. Testing involved pre-test and post-test assessments to gauge proficiency in Arabic vocabulary. In parallel, non-test data was gathered through observation and documentation.Findings – The research findings indicated that the PBL approach in Arabic vocabulary learning exerted a substantial impact and demonstrated greater effectiveness when compared to conventional methods. This was substantiated by the N-Gain Score test results, with the PBL method achieving a score of 0.49, categorized as medium, while the conventional methods scored 0.26, falling into the low category. Research Implications – The implications of this research show that the application of this method can significantly improve students' vocabulary understanding. These findings emphasize the importance of a supportive learning environment and the role of students as active agents in learning. A limitation that needs to be considered in this research is that it focuses on only one school with a limited sample. This means that the generalization of the findings only applies to that context.